The Romantic poetry handbook - O'Neill, Michael 1953-; Callaghan, Madeleine (Wiley Blackwell literature handbooks., 2018)
"This comprehensive survey of British Romantic poetry explores the work of six poets whose names are most closely associated with the Romantic era--Wordsworth, Coleridge, Blake, Keats, Byron, and Shelley--as well as works by other significant but less widely studied poets such as Leigh Hunt, Charlotte Smith, Felicia Hemans, and Letitia Elizabeth Landon. Along with its exceptional coverage, the volume is alert to relevant contexts, and opens up ways of understanding Romantic poetry"-- Provided by publisher.